Which parameters, other than the water content, influence the robustness of cement paste with SCC consistency?. (15th October 2016) - Asghari, Azadehalsadat A.; Ley Hernandez, Aida Margarita; Feys, Dimitri; De Schutter, Geert
Highlights: Robustness of cement pastes with SCC consistency was studied by means of rheology. The amount of water, SP, adding time of SP and mixing speed and time were varied. For mixtures with low w/p, the amount of water and SP have the largest influence. For pastes with higher w/p, the adding time of SP and mixing energy are significant. Factors other than the water content should also be considered to study robustness. Abstract: Robustness is the capacity of cement-based mixtures to tolerate small variations in constituent elements, mixing parameters or temperature. It is an important reason slowing down the practical implementation of self-consolidating concrete (SCC). Especially the sensitivity of fresh SCC properties to a small variation in water content can be found in literature. The influence of the mixing sequence and mixing procedure on the robustness of SCC mixtures is not extensively reported. The present paper evaluates the effect of mixing time, mixing speed and the addition time of superplasticizer on the rheological properties of cement pastes with SCC consistency, which can be related to SCC mixtures. By means of rheology, the changes induced by the variations in mixing procedure are compared to the changes induced by the variations in water and superplasticizer content. The results indicate that changing the water content is the main factor influencing rheology of cement pastes with low water-to-powder ratio (w/p). However, with increased water content in the paste mix design, other factors, such as adding time of the superplasticizer and mixing speed have equal or even superior importance as changing the water content. Dependent on the mix design, it may thus be necessary to use variables other than the water content to study robustness.